Construction of giant glycosidase inhibitors from iminosugar-substituted fullerene macromonomers. Issue 32 (25th May 2017) - Trinh, Thi Minh Nguyet; Holler, Michel; Schneider, Jérémy P.; García-Moreno, M. Isabel; García Fernández, José M.; Bodlenner, Anne; Compain, Philippe; Ortiz Mellet, Carmen; Nierengarten, Jean-François
Abstract : A dramatic enhancement in the glycosidase multivalent inhibitory effect was observed while going from a dodecavalent iminosugar ball to the corresponding giant molecule with 120 peripheral subunits. Abstract : An ultra-fast synthetic procedure based on grafting of twelve fullerene macromonomers onto a fullerene hexa-adduct core was used for the preparation of a giant molecule with 120 peripheral iminosugar residues. The inhibition profile of this giant iminosugar ball was evaluated against various glycosidases. In the particular case of the Jack bean α-mannosidase, a dramatic enhancement of the glycosidase inhibitory effect was observed for the giant molecule with 120 peripheral subunits as compared to that of the corresponding mono- and dodecavalent model compounds.